2013
DOI: 10.1186/1471-2458-13-340
|View full text |Cite
|
Sign up to set email alerts
|

INTEROCC case–control study: lack of association between glioma tumors and occupational exposure to selected combustion products, dusts and other chemical agents

Abstract: BackgroundThe aim was to investigate possible associations between glioma (an aggressive type of brain cancer) and occupational exposure to selected agents: combustion products (diesel and gasoline exhaust emissions, benzo(a)pyrene), dusts (animal dust, asbestos, crystalline silica, wood dust) and some other chemical agents (formaldehyde, oil mist, sulphur dioxide).MethodsThe INTEROCC study included cases diagnosed with glioma during 2000–2004 in sub-regions of seven countries. Population controls, selected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 48 publications
(61 reference statements)
1
18
2
Order By: Relevance
“…The present study observation of the increased risk with the ALAD2 variant for meningioma, but not for glioma or other types, parallels with the observation of Lacourt et al (27) who confirmed the lack of association between glioma tumors and occupational exposure to selected combustion products, dusts and other chemical agents. The only strongly established risk factors for glioma are rare (ionizing radiation and rare medical conditions), possibly rarer compared to the agents that were examined in the present study.…”
Section: Primary Brain Tumorsupporting
confidence: 92%
“…The present study observation of the increased risk with the ALAD2 variant for meningioma, but not for glioma or other types, parallels with the observation of Lacourt et al (27) who confirmed the lack of association between glioma tumors and occupational exposure to selected combustion products, dusts and other chemical agents. The only strongly established risk factors for glioma are rare (ionizing radiation and rare medical conditions), possibly rarer compared to the agents that were examined in the present study.…”
Section: Primary Brain Tumorsupporting
confidence: 92%
“…The vast majority (98%) of occupational histories were obtained from face-to-face interview, with the remaining being obtained from proxy respondents. In a previous analysis from this study in relation to glioma for the same agents, we found no association between oil mists and glioma35; we might have expected to see some excess if there was preferential recall of jobs that involved exposure to oil mists among the cases. However, we have no reason to believe that recall of jobs associated with exposure to mineral oils would have been biased in any way.…”
Section: Discussioncontrasting
confidence: 53%
“…None of the exposures selected showed any significant relationship to glioma with any of three different exposure indices, as reported in Lacourt et al (2013). Selected exposures included solvents, combustion products, metals, and dusts, as well as formaldehyde and sulphur dioxide.…”
Section: Industry and Occupationmentioning
confidence: 91%